2022
DOI: 10.3389/fnins.2022.823701
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Glymphatic System With Diffusion Tensor Imaging-Along the Perivascular Space in Cancer Pain

Abstract: Cancer pain (CP) is one of the most common symptoms affecting life quality, and there is considerable variation in pain experience among patients with malignant tumors. Previously, it has been found that the fluid drainage function in the brain can be regulated by peripheral pain stimulation. However, the relationship between cancer pain and functional changes of the glymphatic system (an important pathway for fluid drainage in the brain) remains unclear. In this study, 97 participants were enrolled, which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The HIT-6 measured the daily life impacts (Supplementary Table 2 in Additional file 1 ) due to RCVS. A recent study revealed that the DTI-ALPS index may be an imaging marker of cancer pain [ 48 ]. Our data further support the potential use of the DTI-ALPS index in the evaluation of subjects with RCVS regarding clinical impacts and implicate the potential role of glymphatics in pain modulation.…”
Section: Discussionmentioning
confidence: 99%
“…The HIT-6 measured the daily life impacts (Supplementary Table 2 in Additional file 1 ) due to RCVS. A recent study revealed that the DTI-ALPS index may be an imaging marker of cancer pain [ 48 ]. Our data further support the potential use of the DTI-ALPS index in the evaluation of subjects with RCVS regarding clinical impacts and implicate the potential role of glymphatics in pain modulation.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study suggested that chronic pain states might also lead to several microstructural and functional changes in the brain. It showed that patients with cancer pain had significantly impaired ISF drainage compared to healthy people 42 . In addition, worse subjective sleep quality is more common in CM people, and studies have established the effectiveness of sleep interventions in reversing CM into EM 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It showed that patients with cancer pain had significantly impaired ISF drainage compared to healthy people. 42 In addition, worse subjective sleep quality is more common in CM people, and studies have established the effectiveness of sleep interventions in reversing CM into EM. 43 Both state of pain and lack of sleep time can cause increased adrenergic signaling, inhibiting the function of the glymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…Using both glymphatic magnetic resonance imaging (MRI) and DTI-ALPS methods, Zhang et al (2021) measured and compared glymphatic clearance function and found a significant correlation between the DTI-ALPS index and the brain glymphatic clearance rate calculated by classical glymphatic MRI, indicating that DTI-ALPS might represent the precise function of brain glymphatic clearance (Siow et al, 2022). The DTI-ALPS index has been used to assess variations in the glymphatic system in several diseases, such as Alzheimer's disease, type 2 diabetes mellitus, idiopathic normal pressure hydrocephalus, Parkinson's disease, cancer pain, and other diseases (Taoka et al, 2017;Yang et al, 2020;Bae et al, 2021;Heo et al, 2021;Ma et al, 2021;Okada et al, 2021;Toh and Siow, 2021a;Wang et al, 2022). Zhang et al (2022) used the DTI-ALPS method in patients with hemorrhagic stroke and found the impairment of the ipsilateral glymphatic system function on the lesion side.…”
Section: Introductionmentioning
confidence: 99%